THE NEED TO BLEED: NARRATIVE AMPLIFICATION OF KILLING SCENES IN “CASTLEVANIA” FROM VIDEO GAME TO TELEVISION SERIES ADAPTATION - Misbah Prayoga; Arista Putri Wulandari; Yuni Tri Fatonah; Dinda Kurnia Aldana; Ariefian Nugra Pradhana; Rofiah Tri Hastuti; Andika Prawijaya; Hakam Munaja (CrossOver Journal of Adaptation Studies, 2023)
In this study, researchers discuss the adaptation from video games to animated films that focus on murder scenes, using Hutcheon's adaptation theory (2012) as a superordinate theory to analyze the adaptation that is present and being amplified from Castlevania video games to Castlevania animated films. Researchers aimed to reveal how Netflix adapted the video game Castlevania into the animated series with the same title through narrative amplification theory by Genette (1997) focused on murder scenes. The research data is in the form of textual-visual, visual-textual, and operative views from adaptation and object sources—data sourced from Castlevania Netflix adaptation and Castlevania gameplay footage. The selected game data source is the object that shows the adaptation and amplification in it. This study focused specifically on the hyper-violent killing scene that was significantly bloodier than the source material. The amplification of violent killing scenes in the adaptation are divided into three parts; Diegetic development, metadiegetic insertion, and extradiegetic intervention. Researchers found that the amplification process that focuses on the murder scenes from the game version is shown with less obvious effects, such as character flashing/blinking and then disappearing. In contrast, the animated version has gone through the amplification process. Blood and violence were shown, and the processes are shown in a more detailed and violent way.